MEDIA SOSIAL INSTAGRAM UNTUK PEMILIHAN TUJUAN WISATA: SIKAP DAN NIAT BERPERILAKU - Gracia Narwastu; Siti Rahayu; Fitri Novika Widjaja (Perpustakaan Universitas Surabaya, 2020)
The purpose of this research is to determine and analyze the influence of social media Instagram on the attitude and behavioural intention of Indonesian tourists in choosing a tourist destination. The results of this study indicate the influence of social media Instagram on the attitude and behavioural intention of Indonesian tourists in choosing a tourist destination. There are 4 of 9 unsupported hypotheses. The supported hypotheses state that the model is clearly theoretically influential. For the unsupported hypotheses show that social media for the choice of tourist destinations does not only use Instagram but can be through other social media such as Facebook, Youtube, Google, and Tripadvisor.